The fifth to die - Barker, J. D. (Jonathan Dylan), 1971- (A 4MK thriller, 2018)
Despite being on the hunt for a new serial killer, Detective Poeter finds himself unable to stay away from the Fourth Monkey case, and quickly becomes obsessed with learning everything about the killer's childhood.